The Spread of Islam in Europe: Historical Patterns and Contemporary Dynamics - Dezi Eldora (GoAcademica Research & Publishing, 2023)
This comprehensive journal article delves into the intricate narrative of the spread of Islam in Europe. It traverses the expansive historical canvas, from early contacts in the 7th century to the present day, and scrutinizes the multifaceted dynamics that have underpinned the diffusion of Islam across the continent. The article scrutinizes how historical legacies, sociocultural interactions, political considerations, and economic factors have interwoven to shape the ever-evolving relationship between Islam and Europe.